Variceal pressure is a strong predictor of variceal haemorrhage in patients with cirrhosis as well as in patients with non-cirrhotic portal hypertension. Issue 4 (1st October 1999) - El Atti, E A; Nevens, F; Bogaerts, K; Verbeke, G; Fevery, J
Abstract : BACKGROUND: Variceal pressure is a strong predictor for a first variceal bleed in patients with cirrhosis. AIMS: To evaluate whether variceal pressure is also a determinant of the risk of a first variceal bleed in patients with non-cirrhotic portal hypertension. METHODS: Variceal pressure was measured non-invasively in 25 patients with non-cirrhotic portal hypertension and large varices while receiving a stable therapeutic regimen. Factors predictive of bleeding were compared with those observed in 87 cirrhotics. RESULTS: The one year incidence of variceal bleeding was 32% (n=28) for the cirrhotic and 20% (n=5) for the non-cirrhotic patients. There was no difference in factors predicting the risk of bleeding between the groups, except for variceal pressure. For the same level of variceal pressure, the risk of variceal bleeding was lower in patients with non-cirrhotic portal hypertension. Multiple logistic regression analysis revealed the following variables as having a significant predictive power: variceal pressure (p=0.0001), red spots (p=0.004), and the time interval between the first observation of the varices and the moment of variceal pressure measurement (p=0.0046). For the non-cirrhotics the risk of bleeding increased with higher Child-Pugh score (p=0.0024); this was not the case for the cirrhotic patients (p=0.9521). CONCLUSION: Variceal pressure is a major predictor of variceal bleeding in patients with cirrhosis as well as in patients with non-cirrhotic portal hypertension. The risk of bleeding in non-cirrhotics is less than in cirrhotics for the same level of variceal pressure. In patients with non-cirrhotic portal hypertension the risk of variceal bleeding increases more with advancing disease.